Fermentation of Rice Straw Using Trichoderma AA1 Mutant With Different Time on Acid Detergent Fiber (ADF) Levels and Neutral Detergent Fiber (NDF) - Sri Sukaryani; Dianto Azar Aswad; Engkus Ainul Yakin (Bantara Journal of Animal Science, 2019)
The aims of this research are: 1) to examine the effect of fermentation time on Acid Detergent Fiber (ADF) and Neutral Detergent Fiber (NDF) levels, 2) to assess the optimal time of fermentation in rice straw using Trichoderma mutant AA1. This research uses a directional pattern design RAL with 4 kinds of treatments and 5 replications. The treatments are T0: Fermented rice straw, T1: Fermented rice straw using AA1 mutant Trichoderma for 7 days, T2: Fermented rice straw using Trichoderma AA1 mutant for 14 days, and T3: Fermented rice straw using Trichoderma AA1 mutant for 7 days, T2: Fermented rice straw using Trichoderma AA1 mutant for 14 days, and T3: Fermented rice straw using Trichoderma AA1 mutant for 7 days 21 days. The observed variables are ADF and NDF levels. The data collected is processed statistically using variance analysis and further tests using the Least Significant Difference Test. The length of time of fermentation has a very significant effect on ADF and NDF levels. The lowest levels were achieved by ADF T3 = 33,962% and the highest at T0 = 54,911% as well as the highest NDF levels at T0 = 64,722% and the lowest at T3 = 50,925%. The results of this research can be concluded that the length of 7-21 days fermentation has a very significant effect on ADF and NDF levels and the optimal time is achieved in rice straw fermentation using Trichoderma AA1 mutant for 21 days.Keywords : fermentation, mutant Trichoderma AA1, rice straw